2017
DOI: 10.1140/epjp/i2017-11292-4
|View full text |Cite
|
Sign up to set email alerts
|

Covariant theory of Bose-Einstein condensates in curved spacetimes with electromagnetic interactions: The hydrodynamic approach

Abstract: We develop a hydrodynamic representation of the Klein-Gordon-Maxwell-Einstein equations. These equations combine quantum mechanics, electromagnetism, and general relativity. We consider the case of an arbitrary curved spacetime, the case of weak gravitational fields in a static or expanding background, and the nonrelativistic (Newtonian) limit. The Klein-Gordon-Maxwell-Einstein equations govern the evolution of a complex scalar field, possibly describing self-gravitating Bose-Einstein condensates, coupled to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 109 publications
(226 reference statements)
2
74
0
Order By: Relevance
“…Recent work by Chavanis with Newtonian gravity solves the Gross–Pitaevskii equation, a variant of Eq. ( 58 ) which involves a pseudo-potential for a Bose–Einstein condensate, to model either dark matter or compact alternatives to neutron stars (Chavanis 2011 , 2012 , 2015 ; Chavanis and Harko 2012 ; Chavanis and Matos 2017 ). However, see a rebuttal to some of this work (Mukherjee et al.…”
Section: Varieties Of Boson Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Chavanis with Newtonian gravity solves the Gross–Pitaevskii equation, a variant of Eq. ( 58 ) which involves a pseudo-potential for a Bose–Einstein condensate, to model either dark matter or compact alternatives to neutron stars (Chavanis 2011 , 2012 , 2015 ; Chavanis and Harko 2012 ; Chavanis and Matos 2017 ). However, see a rebuttal to some of this work (Mukherjee et al.…”
Section: Varieties Of Boson Starsmentioning
confidence: 99%
“…However, note that as mentioned in Sect. 1.1 , ground state BSs can be considered as condensed states of bosons without invoking any analogy (Chavanis 2015 ; Chavanis and Matos 2017 ).…”
Section: Boson Stars In Mathematical Relativitymentioning
confidence: 99%
“…In this sense, the present work is taken to be complementary to those results reported in [13][14][15]. Particularly, this work studies the Klein-Gordon equation of a complex and charged scalar field (with a U(1) symmetry) inside a thermal bath.…”
Section: Introductionmentioning
confidence: 80%
“…(16b) through the third and last terms, which now not only contain factors accounting for the quantum potential, but they also contain factors related to the electromagnetic field and to the relativistic contributions. Also, from (15) it shown that when electromagnetic fields are present, the fluid in question is not longer irrotational since the relation ∇ × v = 0 for the fluid is not longer true.…”
Section: The Hydrodynamical Versionmentioning
confidence: 99%
“…6 See, e.g., Refs. [20][21][22][28][29][30][31] and Sec. XV for the general expression of the KG equation valid for possibly inhomogeneous systems.…”
Section: A Spatially Homogeneous Sfmentioning
confidence: 99%